Validation of An Agile Leadership Instrument For Malaysian School Principals: Application of Content Validity Index (CVI) and Face Validity Index (FVI) Methods - Rashidah binti Mohd Rasul; Mohd Aderi Che Noh; Zulkiple Abd Ghani (Universiti Sains Islam Malaysia, 2026)
International Conference of Language & Education (iLEC2025): Empowering Language and Education to Develop Madani Generation in the Era of Artificial Intelligence (AI) 17 & 18 November 2025 Organized by Universiti Sains Islam Malaysia